Case studies in neuroanesthesia and neurocritical care - Mashour, George A. (George Alexander), 1969-; Farag, Ehab.; ebrary, Inc. (Cambridge : Cambridge University Press, 2011)
"The anesthetic considerations and procedures involved in the perioperative care of the neurosurgical patient are among the most complex in anesthesiology. The practice of neurosurgery and neuroanesthesiology encompasses a wide range of cases, from major spine surgery, to aneurysm clipping and awake craniotomy. Case Studies in Neuroanesthesia and Neurocritical Care provides a comprehensive view of real-world clinical practice. It contains over 90 case presentations with accompanying focussed discussions, covering the broad range of procedures and monitoring protocols involved in the care of the neurosurgical patient, including preoperative and postoperative care. The book is illustrated throughout with practical algorithms, useful tables and examples of neuroimaging. Written by leading neuroanesthesiologists, neurologists, neuroradiologists and neurosurgeons from the University of Michigan Medical School and the Cleveland Clinic, these clear, concise cases are an excellent way to prepare for specific surgical cases or to aid study for both written and oral board examinations"--Provided by publisher.
Machine generated contents note: pt. 1. Neuroanesthesia. section 1. Craniotomy -- pt. 2. Neurocritical care.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Anesthesia in neurology -- Case studies; Nervous system -- Surgery -- Case studies; Neurological intensive care -- Case studies; Electronic books